2023
DOI: 10.30656/jak.v10i1.6144
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis Of Factors Affecting The Financial Distress: The Case Of SOEs In Indonesia

Abstract: The results of company performance can be determined by one of the internal factors of the company, namely the characteristics possessed by the CEO. Echelon theory explains that vision and strategy choices can be influenced by CEO experience and personality which ultimately affect company performance. The motivation for this study is that in Indonesia it is still rare to use a combination of CEO characteristics variables and financial indicators as factors that can affect financial distress in companies. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
0
0
1
Order By: Relevance
“…we fail to reject null and conclude leverage has insignificant effect on distress. Results are in agreement to findings by Mahardini (2023), Dirman (2020), Oktasari (2020) and Bernadin & Tifani (2019) who concluded that leverage had no positive significant effect on distress. The results however, contradicts findings by Marimuthu (2021), Octavia (2021), Ufo (2015), Muin (2020), diyanto (2020 ) and Bahri et.…”
Section:  Effect Of Profitability Leverage and Efficiency On Financi...supporting
confidence: 92%
“…we fail to reject null and conclude leverage has insignificant effect on distress. Results are in agreement to findings by Mahardini (2023), Dirman (2020), Oktasari (2020) and Bernadin & Tifani (2019) who concluded that leverage had no positive significant effect on distress. The results however, contradicts findings by Marimuthu (2021), Octavia (2021), Ufo (2015), Muin (2020), diyanto (2020 ) and Bahri et.…”
Section:  Effect Of Profitability Leverage and Efficiency On Financi...supporting
confidence: 92%
“…Model Taffler menggunakan berbagai rasio keuangan dan variabel nonkeuangan untuk mengidentifikasi perusahaanperusahaan yang berisiko mengalami kebangkrutan. Beberapa rasio keuangan yang digunakan dalam model ini antara lain rasio likuiditas, rasio profitabilitas, rasio utang, dan rasio efisiensi (Yusnita Mahardini, 2023). Selain itu, model ini juga mempertimbangkan variabel non-keuangan seperti ukuran perusahaan, umur perusahaan, dan volatilitas pasar.…”
Section: Model Tafflerunclassified